Low seismic shaking induced densification of large spoil heap composed with low-density particle material - Jian Lv; Tao Jiang; Shuangcheng Wang; Wei Huang; Shenghua Cui; Lihu Duan; Zhenfu Huang (Frontiers in Earth Science)
IntroductionVibration-induced densification of loose particle material is an important phenomenon in deformation and instability study of large spoil heap. To investigate the vibration-induced densification characteristics and deformation mechanisms of a low-density spoil heap under small seismic effects, a spoil heap located in western Sichuan Province was selected as the research subject, and a large-scale shaking table test was performed.MethodsThe settlement and acceleration response behaviors of the slope model during the vibration process were analyzed using three-dimensional point cloud data and acceleration time-history data, with horizontal and horizontal-vertical bi-directional seismic waves applied at progressively increasing amplitudes. Simultaneously, the natural frequency and damping characteristics of the slope model were determined using the transfer function. The deformation and damage modes, as well as the characteristics of vibration-induced densification, were also analyzed and discussed.ResultsThe results indicate that vibration-induced densification of low-density spoil heaps under small seismic forces exists and becomes more pronounced with increasing excitation intensity. This vibration-induced densification leads to a progressively more significant elevation amplification effect.DiscussionDuring the vibration-induced densification process, the medium undergoes self-organization in three phases, including settlement, dynamic equilibrium, and expansion. Based on the experimental observations, the deformation process of low-density spoil heaps can be divided into three stages: settlement and densification, collapse and disintegration, and downward misalignment and slippage. The findings of this study provide valuable insights and recommendations for the prevention and control of low-density spoil heap deformation in future engineering practices.